2012
DOI: 10.1084/jem.20111413
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer progression is controlled by phenotypic changes in dendritic cells

Abstract: Dendritic cells are transformed to become immunosuppressive during ovarian cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
282
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 282 publications
(305 citation statements)
references
References 24 publications
15
282
1
3
Order By: Relevance
“…The immune microenvironment in the advanced mouse breast tumors recapitulates the populations of αβ and γδ T cells, myeloid derived suppressor cells, and macrophages commonly observed in human breast cancer (Figure 4). As we have published previously using adenovirus-Cre to induce ovarian tumors, we found that the viral injection had negligible effect on the corresponding tumor infiltrates and tumor progression 28 . Second, endocrine independent expression of oncogenes ensures that tumor cells have persistently high levels of target gene expression.…”
Section: Discussionsupporting
confidence: 75%
“…The immune microenvironment in the advanced mouse breast tumors recapitulates the populations of αβ and γδ T cells, myeloid derived suppressor cells, and macrophages commonly observed in human breast cancer (Figure 4). As we have published previously using adenovirus-Cre to induce ovarian tumors, we found that the viral injection had negligible effect on the corresponding tumor infiltrates and tumor progression 28 . Second, endocrine independent expression of oncogenes ensures that tumor cells have persistently high levels of target gene expression.…”
Section: Discussionsupporting
confidence: 75%
“…A transgenic ovarian cancer model has exhibited a timedependent downregulation of major histocompatibility complex (MHC) class II and CD40 expression but higher levels of PD-L1 in DCs derived from advanced tumours (435 days, macroscopic tumour mass), as compared with DCs from mice challenged for shorter periods (E7 days) 15 . To examine an advanced tumour condition in lymphoma, we isolated splenic DCs from transgenic diseased Em-Myc mice (ages 3-5 months) and determined their costimulatory molecule surface expression.…”
Section: Progression Of a Myc-driven B-cell Lymphoma Depends On Dcsmentioning
confidence: 99%
“…Although ovarian cancer can be immunogenic, it is generally protected by a suppressive tumor microenvironment that prevents priming of tumor-specific T-cells and suppresses the direct effect of anti-tumor CTLs. 34-36 This environment renders difficult tumor effective resolution by a Th1 response based on CD8 + T-cells through mechanisms of T cell anergy and exhaustion. 37,38 An allergic-like antitumor response has the advantage of having its effectors in the innate immune compartment, not requiring specific priming or generation of CTL immunity, suggesting a unique way to exploit IL-33 in the treatment of peritoneal tumors.…”
Section: Discusionmentioning
confidence: 99%